APLIKASI KOHONEN SELF ORGANIZING PADA TRAVELLING SALESMAN PROBLEM(TSP) DENGAN PROGRAM MATLAB - Ah, Nurul Imamah (J-Proteksion, 2016)
Travelling salesman problem is a problem that founded with sales that must go to many city and rest in a other city until back to the first city. Travelling salesman problem need an optimal ways with minimum scale, untill the process didnt need much money and others. The process to get optimal ways is too difficult, so this article will give the sollution to get an optimal ways with kohonen self organizing and using MATLAB to get an easy program of kohonen self organizing. From the discussion about travelling salesman problem using kohonen self organizing with 10 city and the space, we get minimum space that needed to walk in all the city is 2.6907 meter.Keywords:Travelling Salesman Problem, Kohonen Self Organizing, Matlab